KONTRIBUSI USAHATANI KACANG PANJANG TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI DESA WAREMBUNGAN KECAMATAN PINELENG - Achelien L. Paulus; Welson M. Wangke; Vicky R.B. Moniaga (AGRI-SOSIOEKONOMI, 2015)
This study aims to measure how big the contribution of farming beans on household income of farmers in the village of the District Warembungan, Pineleng Sub-district. Collecting data started from May 2015 to July 2015. Primary data were collected through interviews based on questionnaires and secondary data is data obtained from the Village Government Warembungan and scientific papers related to the study. The data in this research is descriptive analysis and presented in tabular form. The results showed that long bean farming can contribute to the family income of farmers per year in the village of the Warembungan, Village, Pineleng sub-district by 36.33 percent. This suggests that long bean farm income is inportant source of income for farmers who make an important contribution, because the value of long bean farm income to total family income farmers can increase their income more than 35 percent to the total household income of farmers.